Altered Resting-State Functional Activity in Medication-Naive Patients With First-Episode Major Depression Disorder vs. Healthy Control: A Quantitative Meta-Analysis - Ma, Xiaoyue; Liu, Jia; Liu, Taiyuan; Ma, Lun; Wang, Wenhui; Shi, Shaojie; Wang, Yan; Gong, Qiyong; Wang, Meiyun (Frontiers in Behavioral Neuroscience, 2019)
Abstract Background: There is an urgent need for a meta-analysis that characterizes the brain states of major depression disorder (MDD) patients and potentially provides reliable biomarkers, because heterogeneity in the results of resting-state functional neuroimaging has been observed between studies, with some patients not showing the consistent changes, or even opposite patterns. Thus, we evaluated consistent regional brain activity alterations in medication-naive patients with first-episode unipolar MDD and compared the results with those in healthy controls (HCs). Methods: A systematic database search was conducted (in PubMed, Ovid, and Web of Knowledge) between January 1984 and July 2016 to select resting-state functional activity studies with a voxel-wise analysis in MDD. We used anisotropic effect size-signed differential mapping to perform a whole-brain meta-analysis, comparing functional alterations between first-episode medication-naive unipolar MDD patients and HCs by integrating the studies. In addition, subgroup meta-analysis was conducted to control for the MRI analysis method. Moreover, the meta-regression analyses were performed to examine the potential effects of mean age, education duration, illness duration and severity of depressive symptoms. Results: A total of 12 studies were included, comparing 313 MDD patients with 283 HCs. The pooled and subgroup meta-analysis found that the MDD patients showed hyperactivity in the left parahippocampal gyrus, left supplementary motor area, left amygdala, left hippocampus, and left middle frontal gyrus (MFG; orbital part), and hypoactivity in the left lingual gyrus, left middle occipital gyrus, right cuneus cortex, right MFG (orbital part), and left cerebellum. In the meta-regression analyses, the mean illness duration was positively associated with hyper-activation in the left parahippocampal gyrus and hypoactivation in the hemispheric lobule IV/V of the left cerebellum. Conclusions: This meta-analysis indicated that MDD patients had significant and robust resting-state brain activity alteration in amygdala, left hippocampus and other regions, which implicated this finding in the pathophysiology of cognitive and emotional impairment in MDD patients.